The Vehicle for Bringing Positive Education Into the English-As-A-Foreign-Language Classroom: Task-Based Language Teaching - Tamara, Schüszler (Central European Journal of Educational Research, 2022)
The purpose of this article is to provide an overview of the distinctive features of interventions, tasks, and exercises. It is intended to lay theoretical ground to a forthcoming dissertation which is based on action research using positive psychology-based tasks designed or adapted for the secondary English-as-aforeign-language classroom. Therefore, it is essential to first understand the theoretical underpinnings of task-based language teaching and define certain key concepts as well as find the features that distinguish interventions, tasks, and exercises from each other in the language learning classroom. Since literature sometimes refers to these concepts in an interchangeable manner (cf. Seligman et al., 2005; Seligman et al., 2009; Gregersen et al., 2014), an attempt will be made in this theoretical paper to compare them, and then to provide a framework for task descriptions to be used in the dissertation project which is intended to be convergent with current theory and practical enough for teachers.